PSXVII-32 Late-Breaking: Weaning of ad libitum fed dairy calves with automated feeders using fixed and individual methods. - Welboren, A (J Anim Sci, 2018)
The increasing availability of automated milk dispensers on dairy farms facilitates ad libitum milk supply but weaning calves from high milk allowances is a challenging process. This study evaluated different gradual weaning methods for their impact on starter intake and growth. Thirty-six Holstein (n = 30) or crossbred (n = 6) bull calves were individually housed from d 2–14 of age and had ad libitum access to milk replacer from teat buckets. From d 15–84 of age, calves were grouped and had ad libitum access to milk replacer, starter, straw and water from automated feeders. At d 35, calves were blocked (age and breed), and randomly assigned to a weaning method: (1) Linear (LIN), milk supply was stepped down to 6 L/d on d 36, and linearly reduced between d 36 and 63 from 6 to 2 L/d. (2) Step-down (STEP), milk supply was stepped down to 6 L/d from d 36–48, 4 L/d from d 49–56 and 2 L/d from d 57–63. (3) Dynamic (DYN), at d 36, milk supply was reduced for each individual calf to 75% of the average voluntary consumption between d 29–35, then maintained for 9 d, and then reduced to 50% for 10 d, and to 25% for 9 d. DYN calves received more milk during weaning than LIN calves, whereas STEP calves had intermediate milk intake. Starter intake was not affected by weaning method. DYN calves grew faster and were heavier than STEP calves during post-weaning period, whereas LIN calves performed similarly to DYN calves (1.329 ± 0.082, 1.099 ± 0.082 and 1.228 ± 0.082 kg/d; 123.5 ± 2.41, 116.6 ± 2.41 and 120.4 ± 2.41 kg at d 84). These results highlight the post-weaning benefits of DYN and LIN weaning methods when compared with more abrupt step-down strategies.